2021
DOI: 10.1371/journal.pone.0251519
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pulmonary tuberculosis among the tribal populations in India

Abstract: Importance There is no concrete evidence on the burden of TB among the tribal populations across India except for few studies mainly conducted in Central India with a pooled estimation of 703/100,000 with a high degree of heterogeneity. Objective To estimate the prevalence of TB among the tribal populations in India. Design, participants, setting A survey using a multistage cluster sampling design was conducted between April 2015 and March 2020 covering 88 villages (clusters) from districts with over 70% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
3
18
1
Order By: Relevance
“…Similar findings of high TB burden have been reported among indigenous population globally [21,22]. In India, studies conducted in other indigenous groups reported TB prevalence rates ranging from 133 to 840 per 100 000 in different parts of the country [5,11,[23][24][25][26]. Our finding highlights an alarmingly high level of bacteriologically confirmed PTB incidence in this disadvantaged community.…”
Section: Discussionsupporting
confidence: 88%
“…Similar findings of high TB burden have been reported among indigenous population globally [21,22]. In India, studies conducted in other indigenous groups reported TB prevalence rates ranging from 133 to 840 per 100 000 in different parts of the country [5,11,[23][24][25][26]. Our finding highlights an alarmingly high level of bacteriologically confirmed PTB incidence in this disadvantaged community.…”
Section: Discussionsupporting
confidence: 88%
“…Most of the studies have focussed on a particular disease/health condition. In the present study, 5.2 per cent of the participants aged ≥18 yr had symptoms suggestive of pulmonary TB, which is slightly higher as compared to the reports of previous studies (ranging from 2.1 to 3.6%) 21 , 22 . A study by Patwa et al 23 among the tribal population of Gujarat stated hypertension (4.5%), diabetes (1.7%) and cardiovascular diseases (1.6%) as commonly reported morbidities 23 .…”
Section: Discussioncontrasting
confidence: 82%
“…Alcohol consumption was associated with an increased risk of tuberculosis in all meta-analyses 24 .A population-based case control study in South India demonstrated an increased incidence of pulmonary TB among those who smoke and drink 25 .The malnutrition assessed from the estimated values of Body Mass Index (BMI)in the studyrevealed that the chest symptomatic are more among the under nourished respondents. The findings that alcohol, smoking, and low BMI are significantly related to the higher prevalence of TB among the tribal populations in India 26 that reemphasised in our study as well.…”
Section: Discussionsupporting
confidence: 70%